Kemampuan Pemahaman Konsep pada Materi Sistem Persamaan Linear Dua Variabel Berdasarkan Teori APOS Bagi Siswa SMP - Ferdi F Kadafuk; Kristoforus Djawa Djong; Irmina Veronika Uskono (Universitas Muria Kudus, 2020)
his research is a qualitative research that aims to analyze the understanding of mathematical concepts of students of one of the yunior high school in Kupang city in problem solving on the material system of two-variable linear equations. The subjects in this study were three students of class VIII who had high ability, medium ability, and low ability. The selection of subjects were based UTS results and discussions with mathematics teacher. Data collected in the form of data on the results of problem solving tasks and the results of interviews based on indicators of understanding of the concept. Data analysis includes data reduction, data presentation, and drawing conclusions. Checking the validity of the data using time triangulation. After the data is presented and analyzed, it can be concluded that (1) Students with high ability results are able to solve the given problems and meet the indicators of the ability to understand concepts based on APOS theory. (2) Students with medium ability results are fulfilling the ability to understand concepts based on APOS theory. (3) While students with low ability results do not meet the indicators of the ability to understand concepts based on APOS theory.